2015
DOI: 10.1080/14786435.2015.1015469
|View full text |Cite
|
Sign up to set email alerts
|

Generalized balanced power diagrams for 3D representations of polycrystals

Abstract: Characterizing the grain structure of polycrystalline material is an important task in material science. The present paper introduces the concept of generalized balanced power diagrams as a concise alternative to voxelated mappings. Here, each grain is represented by (measured approximations of) its center-of-mass position, its volume and, if available, by its second-order moments (in the non-equiaxed case). Such parameters may be obtained from 3D x-ray diffraction. As the exact global optimum of our model res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
78
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(78 citation statements)
references
References 41 publications
0
78
0
Order By: Relevance
“…These models are based on isotropic or anisotropic grain growth, where the tessellations are constructed on the basis of an initial approximation of the grains by balls or ellipsoids. Optimized methods for fitting these models to real data were presented in Alpers et al (2015), Teferra and Graham-Brady (2015) anď Sedivý et al (2016). These results have shown that, in particular, the ellipsoid-based tessellation models are able to describe a great variety of grain microstructures with very high precision.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…These models are based on isotropic or anisotropic grain growth, where the tessellations are constructed on the basis of an initial approximation of the grains by balls or ellipsoids. Optimized methods for fitting these models to real data were presented in Alpers et al (2015), Teferra and Graham-Brady (2015) anď Sedivý et al (2016). These results have shown that, in particular, the ellipsoid-based tessellation models are able to describe a great variety of grain microstructures with very high precision.…”
Section: Introductionmentioning
confidence: 92%
“…Such methods were presented, e.g., in Alpers et al (2015); Teferra and Graham-Brady (2015). However, they are difficult to apply to large data sets.…”
Section: Model Fittingmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic Voronoi tessellation [5] is often too simple to be used for fitting polycrystals [18], on the other hand the Laguerre tessellation [12] became quite popular for microstructures with approximately convex grains [13], [23]. More complex models exhibiting anisotropy or curved boundaries [1], [22] rely on higher-dimensional marks and are thus more difficult to handle.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has the advantage that techniques established for fitting tessellation models to foams (Redenbach, ; Liebscher & Redenbach, ) can be exploited for fitting the model to observed microstructures. Furthermore, the same model class and fitting techniques can also be used for modelling the grain structure of the aluminium matrix (Fritzen et al ., ; Alpers et al ., ; Šedivý et al ., ). Finally, also intermetallic precipitates can be incorporated in our microstructure model.…”
Section: Introductionmentioning
confidence: 99%